Strategi Pencegahan Kebakaran Hutan dan Lahan di Kesatuan Pengelolaan Hutan Kubu Raya, Ketapang Selatan, dan Ketapang Utara di Provinsi Kalimatan Barat - Rachman, Arief; Saharjo, Bambang Hero; Putri, Eka Intan Kumala (Jurnal Ilmu Pertanian Indonesia, 2020)
West Kalimantan Province, Indonesia, is an area that is crossed by the equator and its territory is mostly peat area. The aim of this study was to examine the impact of losses due to forest and land fires and srategies for preventing forest and land fires in the Forest Management Unit (FMU) in West Kalimantan Province. This research was conducted from May to October 2018 in the FMU Kubu Raya, the FMU South Ketapang, and FMU North Ketapang. The research method used was descriptive method. Vegetation Data were measured with the stratified random sampling in 20 x 100 m transect. Social economic data were taken by using 30 respondents from 6 vilages with based on purposive sampling. Data analysis regarding losses due to forest and land fires was performed using the economic valuation value analysis while forest and land fires’ prevention strategies in the FMUs were determined using SWOT and IE (Internal-External) Matrix. The results showed that the area of forest and land fires reached 50 ha with a total loss of IDR 8 billion. Forest and land fire prevention strategies using SWOT were determined in the growing and developing parts with the implemented alternative strategies, i.e., intensive and integrative. Keywords: economic valuation, forest management, peatland, SWOT, West Kalimantan